Strong turbulent flow in the subauroral region in the Antarctic can deteriorate satellite-based navigation signals - Kotova, D. S.; Sinevich, A. A.; Chernyshov, A. A.; Chugunin, D. V.; Jin, Y.; Miloch, W. J. (Scientific Reports, 2025)
In the subauroral zone at the boundary of the auroral oval in the evening and night hours during geomagnetic disturbances, a narrow (about 1°–2°) and extended structure (several hours in longitude) is formed. It is known as a polarization jet (PJ) or the subauroral ion drift (SAID). The PJ/SAID is a fast westward ion drift and is one of the main signatures of a geomagnetic disturbance in the subauroral ionosphere at the altitudes of the F-layer, when the geomagnetic AE index reaches more than 500 nT. Plasma speed in the PJ/SAID can reach several kilometres per second, and the size of plasma irregularities inside it can reach scales from tens of meters to several hundred meters. Such high velocities and structured plasma can affect trans-ionospheric radio waves and lead to scintillations in the received signal. We show that at the moment of auroral activity intensification, an increase in the magnitude of phase scintillation index (σϕ) as well as loss of satellite signals lock were observed in the region of the PJ/SAID equatorward of the auroral oval over Dronning Maud Land (Queen Maud Land) in Antarctica. We find that fluctuations inside the PJ/SAID can lead to serious deterioration of radio communication or navigational services. We emphasize the importance of considering the geometry of the beam passing from the GNSS satellite to the receiver on the ground. We highlight the mutual contribution of the PJ/SAID and the diffuse aurora boundary, which are almost impossible to separate in practice. Our results demonstrate the importance of considering the subauroral zone, where very dynamic plasma formations can occur with a strong flow and various-scale irregularities inside that lead to serious interference in satellite communications.
Keywords: Dronning Maud Land; aurora; fysikk; geomagnetiske stormer; ionosfæren; magnetosfæren; romfysikk; sørlys

Interhemispheric Asymmetry of Large-Scale Electron Density Gradients in the Polar Cap Ionosphere: UT and Seasonal Variations - Jin, Yaqi; Xiong, Chao (Journal of Geophysical Research: Space Physics, 2020)
The high-latitude ionosphere is highly dynamical with significant irregularities and density gradients. However, the spatial and temporal distributions of density gradients and irregularities are very different between the Arctic and Antarctic. In this report, we study the interhemispheric asymmetry of the large-scale (100 km) density gradients in both polar caps. Our results show that density gradients in the Arctic are enhanced during local winter (December solstice) with a peak around 19 UT. The UT and spatial distributions in the Antarctic local winter (June solstice) are similar to the Arctic except that they are reversed by 12 hr, which indicates a mirror symmetry between hemispheres. The 12-hr difference in the peak density gradients can be explained by the displacements between the geographic and geomagnetic poles. The only asymmetry (anomaly) is the persistence of strong density gradients in the southern polar cap during local summer (December solstice).
Keywords: Antarktis; fysikk; geovitenskap; ionosfæren; polarområdene

SuperDARN Radar-Derived HF Radio Attenuation During the September 2017 Solar Proton Events - Bland, Emma C; Heino, Erkka; Kosch, Michael J; Partamies, Noora (Space Weather, 2018)
Two solar proton events in September 2017 had a significant impact on the operation of the Super Dual Auroral Radar Network (SuperDARN), a global network of high-frequency (HF) radars designed for observing F region ionospheric plasma convection. Strong polar cap absorption caused near-total loss of radar backscatter, which prevented the primary SuperDARN data products from being determined for a period of several days. During this interval, the high-latitude and polar cap radars measured unusually low levels of background atmospheric radio noise. We demonstrate that these background noise measurements can be used to observe the spatial and temporal evolution of the polar cap absorption region, using an approach similar to riometry. We find that the temporal evolution of the SuperDARN radar-derived HF attenuation closely follows that of the cosmic noise absorption measured by a riometer. Attenuation of the atmospheric noise up to 10 dB at 12 MHz is measured within the northern polar cap, and up to 14 dB in the southern polar cap, which is consistent with the observed backscatter loss. Additionally, periods of enhanced attenuation lasting 2–4 hr are detected by the midlatitude radars in response to M- and X-class solar flares. Our results demonstrate that SuperDARN's routine measurements of atmospheric radio noise can be used to monitor 8- to 20-MHz radio attenuation from middle to polar latitudes, which may be used to supplement riometer data and also to investigate the causes of SuperDARN backscatter loss during space weather events.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; ionosfæren; polarområdene; radiostøy

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

The impact of sunlight on high-latitude equivalent currents - Laundal, Karl M; Gjerloev, Jesper; Østgaard, Nikolai; Reistad, Jone Peter; Haaland, Stein; Snekvik, Kristian; Tenfjord, Paul; Ohtani, Shin-ichi; Milan, Steve (Journal of Geophysical Research: Space Physics, 2016)
Ground magnetic field measurements can be mathematically related to an overhead ionospheric equivalent current. In this study we look in detail at how the global equivalent current, calculated using more than 30 years of SuperMAG magnetometer data, changes with sunlight conditions. The calculations are done using spherical harmonic analysis in quasi-dipole coordinates, a technique which leads to improved accuracy compared to previous studies. Sorting the data according to the location of the sunlight terminator and orientation of the interplanetary magnetic field (IMF), we find that the equivalent current resembles ionospheric convection patterns on the sunlit side of the terminator but not on the dark side. On the dark side, with southward IMF, the current is strongly dominated by a dawn cell and the current across the polar cap has a strong dawnward component. The contrast between the sunlit and dark side increases with increasing values of the F10.7 index, showing that increasing solar EUV flux changes not only the magnitude but also the morphology of the equivalent current system. The results are consistent with a recent study showing that Birkeland currents indirectly determine the equivalent current in darkness and that Hall currents dominate in sunlight. This has implication for the interpretation of ground magnetic field measurements and suggests that the magnetic disturbances at conjugate points will be asymmetrical when the solar illumination is different.
Keywords: Antarktis; geomagnetiske stormer; ionosfæren; ionosfæriske strømmer; polarlys; polarområdene; sollys; solvind

Interhemispheric differences in ionospheric convection: Cluster EDI observations revisited - Förster, Matthias; Haaland, Stein (Journal of Geophysical Research: Space Physics, 2015)
The interaction between the interplanetary magnetic field and the geomagnetic field sets up a large-scale circulation in the magnetosphere. This circulation is also reflected in the magnetically connected ionosphere. In this paper, we present a study of ionospheric convection based on Cluster Electron Drift Instrument (EDI) satellite measurements covering both hemispheres and obtained over a full solar cycle. The results from this study show that average flow patterns and polar cap potentials for a given orientation of the interplanetary magnetic field can be very different in the two hemispheres. In particular during southward directed interplanetary magnetic field conditions, and thus enhanced energy input from the solar wind, the measurements show that the southern polar cap has a higher cross polar cap potential. There are persistent north-south asymmetries, which cannot easily be explained by the influence of external drivers. These persistent asymmetries are primarily a result of the significant differences in the strength and configuration of the geomagnetic field between the Northern and Southern Hemispheres. Since the ionosphere is magnetically connected to the magnetosphere, this difference will also be reflected in the magnetosphere in the form of different feedback from the two hemispheres. Consequently, local ionospheric conditions and the geomagnetic field configuration are important for north-south asymmetries in large regions of geospace.
Keywords: Antarktis; astrofysikk; geovitenskap; ionosfæren; magnetosfæren; polarområdene; solvind

Birkeland current effects on high-latitude ground magnetic field perturbations - Laundal, Karl M; Haaland, Stein; Lehtinen, N; Gjerloev, Jesper; Østgaard, Nikolai; Tenfjord, Paul; Reistad, Jone Peter; Snekvik, Kristian; Milan, Steve; Ohtani, Shin-ichi; Anderson, B J (Geophysical Research Letters, 2015)
Magnetic perturbations on ground at high latitudes are directly associated only with the divergence-free component of the height-integrated horizontal ionospheric current, J⊥,df. Here we show how J⊥,df can be expressed as the total horizontal current J⊥ minus its curl-free component, the latter being completely determined by the global Birkeland current pattern. Thus, in regions where J⊥=0, the global Birkeland current distribution alone determines the local magnetic perturbation. We show with observations from ground and space that in the polar cap, the ground magnetic field perturbations tend to align with the Birkeland current contribution in darkness but not in sunlight. We also show that in sunlight, the magnetic perturbations are typically such that the equivalent overhead current is antiparallel to the convection, indicating that the Hall current system dominates. Thus, the ground magnetic field in the polar cap relates to different current systems in sunlight and in darkness.
Keywords: Antarktis; Birkelandstrømmer; ionosfæren; ionosfæriske strømmer; polarområdene; sollys

Self-scattering of a powerful HF radio wave on stimulated ionospheric turbulence - Zalizovski, Andriy; Kashcheyev, S B; Yampolski, Y M; Galushko, V G; Belyey, Vasyl; Isham, B; Rietveld, M T; La Hoz, C; Brekke, A; Blagoveshchenskaya, N F; Kornienko, V A (Radio Science, 2009)
An analysis is presented of high-frequency (HF) signals from the European Incoherent Scatter HF ionospheric modification transmitter received during 26–30 October 2002 at three sites, two in Europe and one in Antarctica. Two components with different characteristics (“mirror-reflected” and “scattered”) were observed in the signal spectra. The mirror-reflected component can be associated with radiation through the side lobes of the transmitting antenna thus bypassing the modified volume on its way to the receiving sites. In contrast, the scattered component was radiated through the main antenna beam and then scattered by pump-induced ionospheric irregularities above the heater. As a result, variations in the scattered component signal intensity and Doppler frequency shifts (DFS) recorded at the greatly separated sites showed a high level of correlation. It is shown that the Doppler frequency variations can be associated with variations in the plasma density and/or physical motion velocities of stimulated inhomogeneities within the volume common to all propagation paths. Analysis of Doppler frequency shifts at greatly separated sites would allow identifying the mechanism responsible for the self-scattering effect. In the case of DFSs due to motion of the pump-induced scatterers it would be also possible to reconstruct the full velocity vector of the inhomogeneities.
Keywords: Antarktis; astronomi; fysikk; ionosfæren; polarområdene

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene